Determinants of the State Railway of Thailands (SRT) Total Quality Management process: SEM analysis - Tanin Sivalai; Nuttawut Rojniruttikul (My University, 2018)
Dropping from the peak of 88 million passengers back in 1994, Thailand's state railway system today is transporting less than 50% of its maximum.Operations run at a loss, with infrastructure and aged equipment contributing to significant delays and a continuing loss of passengers.In late 2017 however, a new 20-year, $US81.57billion plan was proposed to save the SRT from its downward spiral.The researchers therefore undertook a study to survey 500 Thai state railway (SRT) civil servants.Each was given a 5-level Likert-type agreement scale questionnaire, containing 51 items concerning their personal characteristics, their attitudes, human resource management processes, the use of the balanced scorecard for improvement, their perspectives on SRT's organizational culture, and the SRT's total quality management program.LISREL 9.1 was used to conduct a confirmatory factor analysis (CFA) and then structural equation model (SEM) was applied to analyze the results.The results have determined that organizational culture had the greatest impact on total quality management, followed by attitudes, human resource management, and finally, the balanced scorecard.It is also interesting to note that the surveyed SRT staff consider organizational change as the most important aspect in improving efficiency, while staff evaluation and reward system were rated as least effective for total quality management.
Keywords: Quality and Supply Management